2007
DOI: 10.1074/jbc.m700447200
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-activated Receptor γ Up-regulates the Bcl-2 Anti-apoptotic Protein in Neurons and Induces Mitochondrial Stabilization and Protection against Oxidative Stress and Apoptosis

Abstract: Peroxisome proliferator-activated receptor ␥ (PPAR␥) has been proposed as a therapeutic target for neurodegenerative diseases because of its anti-inflammatory action in glial cells. However, PPAR␥ agonists prevent ␤-amyloid (A␤)-induced neurodegeneration in hippocampal neurons, and PPAR␥ is activated by the nerve growth factor (NGF) survival pathway, suggesting a neuroprotective anti-inflammatory independent action. Here we show that the PPAR␥ agonist rosiglitazone (RGZ) protects hippocampal and dorsal root ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
190
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 224 publications
(206 citation statements)
references
References 74 publications
13
190
1
2
Order By: Relevance
“…This is important because increased levels of nitrated proteins have been reported in AD brains and cerebrospinal fluid of AD patients, 43 and numerous proteins in AD have been shown to be nitrated by peroxynitrite. 44 For example, peroxisome proliferator-activated receptor gamma expression protects neurons from Abmediated toxicity; 45 however, its nitration prevents its translocation to the nucleus, thereby preventing mitochondrial biogenesis. 46 We also found that nanoceria blocked Ab-mediated mitochondrial fragmentation via a mechanism that involved reduction of DRP1 S616 hyperphosphorylation (Figure 5b).…”
Section: Discussionmentioning
confidence: 99%
“…This is important because increased levels of nitrated proteins have been reported in AD brains and cerebrospinal fluid of AD patients, 43 and numerous proteins in AD have been shown to be nitrated by peroxynitrite. 44 For example, peroxisome proliferator-activated receptor gamma expression protects neurons from Abmediated toxicity; 45 however, its nitration prevents its translocation to the nucleus, thereby preventing mitochondrial biogenesis. 46 We also found that nanoceria blocked Ab-mediated mitochondrial fragmentation via a mechanism that involved reduction of DRP1 S616 hyperphosphorylation (Figure 5b).…”
Section: Discussionmentioning
confidence: 99%
“…28 Based on the observation that Aldo-induced ROS originated from mt, we investigated if Aldo induced MtD. The mt ultrastructure morphology of Aldo-treated cells displayed mt vacuolization and decreased distribution in podocytes ( Figure 4A).…”
Section: Aldo-induced Mtd In Podocytes Via Mrmentioning
confidence: 99%
“…The images were analyzed with LCS Leica confocal software and recorded as mean MitoRed or TMRM fluorescence signal per live cell. Estimation of fluorescence intensities were presented as the pseudoratio (⌬F/F o ), which was calculated using the following formula: ⌬F/F o ϭ (F Ϫ F base )/(F base Ϫ B), where F is the measured fluorescence intensity of the indicator, F base is the fluorescence intensity before the stimulation, and B is the background signal determined from the average of areas adjacent to the cells (22,28,30).…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial Potential Determination in Live CellsMitochondria membrane potential was determined using Mitotracker Red CM-H 2 XRos (MitoRed) or TMRM (22,28,30). Striatal cells were grown on poly-L-lysine-coated plates and cultured for 4 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation